Breastfeeding duration modifies the effect of smoking during pregnancy on eczema from early childhood to adolescence. Issue 12 (29th November 2018) - Mukherjee, Nandini; Sutter, Thomas R.; Arshad, Syed Hasan; Holloway, John W.; Zhang, Hongmei; Karmaus, Wilfried
Abstract: Background: Cigarette smoke contains compounds similar to coal tar, an ancient remedy of eczema. Some studies have reported protective effects of maternal gestational smoking on offspring eczema; however, others have shown no or increased risks. Similarly, studies linking breastfeeding duration and eczema have demonstrated contradictory findings. No study has yet investigated combined effects of these two factors on eczema. Objective: Since tobacco compounds can pass to offspring via breast milk, we investigated their combined effects on eczema development from childhood to adolescence. Methods: We obtained information regarding gestational smoking, exclusive breastfeeding duration, and eczema at ages 1‐or‐2, 4, 10, and 18 years from the Isle of Wight (IOW) birth cohort, UK. Using generalized estimating equations, we assessed the interaction of gestational smoking and residual exclusive breastfeeding duration (Resid‐BF‐duration, obtained by regressing the latter on maternal smoking) on eczema over time adjusting for confounders. For the three transition periods of 1‐or‐2 to 4 years, 4‐10, and 10‐18 years, we estimated risks of persistent, incident, and remitting eczema associated with the interaction using repeated measurements. Results: If the mother smoked during gestation, longer Resid‐BF‐duration was associated with a lower risk of eczema, compared to if she did not smoke. The risk ratios (95% CI) if the mother smoked during gestation and exclusively breastfed for at least 3, 9, 15, 21 weeks are 0.7 (0.6, 1.7), 0.6 (0. 4, 0.9), 0.5 (0.3, 0.8), and 0.4 (0.2, 0. 8), respectively. Additionally, in all three transition periods, the risk of persistent eczema was lower with longer Resid‐BF‐duration if the mother smoked during gestation. Conclusions and Clinical Relevance: Results suggest a protective effect of gestational smoking combined with longer duration of exclusive breastfeeding on early‐onset persistent eczema. Future studies should examine underlying biological mechanisms. Prolonged breastfeeding should be encouraged even if the mother smoked during gestation.